2012
DOI: 10.5539/ijef.v4n6p78
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Conservatism in Accounting Policies and Its Effect on Earnings Management

Abstract: This study investigates the level of conservatism in accounting policies and examines its effect on earnings management for a sample of 259 Jordanian Manufacturing companies during the period 2006-2009. The results indicate that there are differences on the level of conservatism between companies. Furthermore, the results of this study reveal that conservatism and size are negatively related to earnings management, whereas performance found to be positively related to earnings management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Lara, Osma, and Penalva (2012) found that the firms, which are more conservative have less chances of being engaged in EM. Similarly, another study by (Abed, Al-Badainah, & Serdaneh, 2012) showed that accounting conservatism and the size are inversely related to EM. While, Lobo, Parthasarathy, and Sivaramakrishnan (2008) said that the financial statements following conservative approach have more EM and show a positive relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Lara, Osma, and Penalva (2012) found that the firms, which are more conservative have less chances of being engaged in EM. Similarly, another study by (Abed, Al-Badainah, & Serdaneh, 2012) showed that accounting conservatism and the size are inversely related to EM. While, Lobo, Parthasarathy, and Sivaramakrishnan (2008) said that the financial statements following conservative approach have more EM and show a positive relationship.…”
Section: Introductionmentioning
confidence: 99%
“…in such level of applying conservatism may increase the possibility of manipulation in the financial reports and will be more likely to practice earning management. Al-Zoubi (2012) and Abed et al (2012) found evidences on the existence of earning management in financial reports of Jordanian companies. In a similar vein, the World Bank and International Monetary Fund (IMF) in 2004 have evaluated the status of corporate governance in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…The low level of conservatism of Jordanian listed firms was attributed amongst others to the poor of corporate governance practices (Abed et al, 2012;Hamdan, 2012a). in such level of applying conservatism may increase the possibility of manipulation in the financial reports and will be more likely to practice earning management.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this study, discretionary accruals of high level function as the earning management practices' indicator. The modified Jones model has been chosen in this study for earning management measurement because many past researches have proven the accuracy and robustness of this model in the computation of discretionary accruals when compared to other available models (Guay, Kothari, & Watts, 1996;Abed, Al-Badainah, & Serdaneh, 2012).…”
Section: Tac = Net Income (Ni) -Cash Flow From Operation (Cf)mentioning
confidence: 99%
“…As suggested, corporate managers seek to earnings management practices for attaining some capital market and contractual objectives. These include evading debt covenants violation, raising their compensation share, fulfilling or going beyond the expectations of analysists and also, smoothing the reported earnings (Abed, Al-Badainah & Serdaneh, 2012;Al-Sraheen, 2016) It is common for the practices of earnings management to lead to grave corporate fraud. For instance, the subprime mortgage crisis that happened in 2007 caused grave crisis to the world economy while est ablished firms including Lehman Brothers and Merry Lynch were pushed into bankruptcy owing to the managers' practice of earnings management.…”
Section: Introductionmentioning
confidence: 99%